Lakon Karna Gugur sebuah Pengorbanan untuk Kejayaan Pandawa - Sukatno Sukatno (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
In the world of puppetry, lakon Karna Gugur contains moral teachings with values that can be seen through the characters of Basukarna and Duryudana in defending the Astina State. This study aims to explain Karna's character in his efforts to win goodness. Structural analysis is used to achieve this goal. Karna as a symbol of virtue can be understood through the lakon Karna Gugur in the Baratayuda series. From the moral aspect, the characters of Basukarna and Duryudana represent the transformations of good and evil. The good done by Karna is a sign of his service to Astina's country, while the evil is symbolized by Duryudana with the attitude of defending the country to the end.